Age‐related morphological changes in the pancreas and their association with pancreatic carcinogenesis. Issue 8 (24th July 2019) - Matsuda, Yoko
Abstract : Age‐related pathological changes in the pancreas have been unclear because they are often minor and nonspecific. However, recent studies have shown that they are closely related to various pathological conditions such as pancreatic cancer and diabetes mellitus. Knowledge of age‐related changes is important to determine appropriate prevention, detection, and treatment strategies for various diseases observed in elderly patients. We present a review of the pathological age‐related non‐neoplastic changes in the exocrine pancreas such as pancreatic fatty replacement, lobulocentric pancreatic atrophy, pancreatic duct ectasia, and metaplasia of exocrine pancreas, as well as changes in islet cells. We have discussed common pancreatic neoplasms in elderly patients, such as pancreatic intraepithelial neoplasia (PanIN), intraductal papillary mucinous neoplasms (IPMNs), and pancreatic ductal adenocarcinoma (PDAC). Age‐related pathological changes play a key role in pancreatic carcinogenesis via telomere dysfunction. Further studies are warranted to clarify molecular mechanisms of pancreatic carcinogenesis in elderly patients.